PEMBINAAN WARGA GEREJA BAGI PEMUDA DI ERA GLOBALISASI - Bella Sinambela; Benita Ariany Nainggolan; Febrianti Sagala; Friska Elisabet Tampubolon; Irmawaty Togatorop; Andar Gunawan Pasaribu (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2022)
Literature review to explain the development of church members for young people, to play an active role in the church in the current era of globalization, which seeks to get young people to take an active role and participate in serving God in church organizations, by reflecting the character of God and glorify God. so the author uses a formal analysis with an emphasis on contextualization with informed publications, so the development of church members for young people, to play an active role in the church in the current era of globalization is very important.